Regulation of adhE (Encoding Ethanol Oxidoreductase) by the Fis Protein in Escherichia coli - Membrillo-Hernández, Jorge (American Society for Microbiology, 1999)
The adhE gene of Escherichia coli encodes a multifunctional ethanol oxidoreductase whose expression is 10-fold higher under anaerobic than aerobic conditions. Transcription of the gene is under the negative control of the Cra (catabolite repressor-activator) protein, whereas translation of the adhE mRNA requires processing by RNase III. In this report, we show that the expression of adhE also depends on the Fis (factor for inversion stimulation) protein. A strain bearing a fis::kan null allele failed to grow anaerobically on glucose solely because of inadequate adhE transcription. However, fis expression itself is not under redox control. Sequence inspection of the adhE promoter revealed three potential Fis binding sites. Electrophoretic mobility shift analysis, using purified Fis protein and adhE promoter DNA, showed three different complexes.